Modelo de apuração de resultados fundamentado na gestão econômica aplicado às empresas produtoras de confecções - Costa, Lucy Mary Carvalho (2006)
This paper aims mainly to design an income calculation model based in the concepts of the economic administration for the clothing producer companies, starting from the identification of the main economic events from their productive cycle, generating important, opportune and useful information for the improvement of the economic results of these organizations. The model was elaborated from a descriptive research applied to the productive process, to the main economic events of a clothing producer company of the Metropolitan Area of Fortaleza, State of Ceará, using the technique of direct observation, focused interviews and application of a questionnaire. A bibliographical research was used as theoretical support, initially on the clothing sector, in order to withdraw specific information on this productive sector. Later on, it was researched on the concepts and procedures of the Economic Administration-GECON, which was the basis for the configuration of the model, from a systemic vision of the clothing producer company, that has as application object the transactions of the main economic events of the activities of these companies’ productive cycle. The model demonstrates the physical, financial, economic and patrimonial impacts of each event/transaction, in the moment of its occurrence, considering as transfer price the cost of opportunity of the obtained resources and sacrificed by the several activities in the productive cycle of these companies. The model still demonstrates the accrued wealth in each event/transaction, evidencing the contribution of each activity and responsability area for the income of the company. The income calculated by the model was analyzed comparatively with the result obtained by the traditional accounting information system, according to the fundamental principles of accounting, used in the researched company, being evidenced qualitative differences between both, with positive prominence for the proposed model in the generation of precise and useful information for the improvement of the process of managerial administration. The conclusion is that the model of income calculation based in the economic administration is compatible with the operational reality of the clothing producer companies, it demonstrates the effective contribution of the transactions, activities and responsability areas to the global income of these companies and it generates important, opportune and useful information for the improvement of the economic income of these organizations.